O fazer científico dos sujeitos criativos : indicadores de altas habilidades/superdotação nos artosta do boi-bumbá de Parintins - Oliveira, Geysykaryny Pinheiro de (2018)
This research approaches giftedness indicators on Boi-Bumbá artists from Parintins, through their cientific practices visible on the art produced by them. By investigating subjects who present above average skills in any area of the knowledge, it’s possible to verify whether they are Highly Skilled subjects, thus these individuals remain invisible to society most of the times. Beyond that, these individuals enhanced skills might intertwine with science teaching, once they might be related to areas that integrate the resume, such as Mathematics, Physics, Chemistry, Biology, among other areas. The goal of this research was to analyze giftedness behaviors manifested by Boi-Bumbá artists from Parintins in their artistic expressions. The research is Qualitative and Phenomenological. Field research was adopted as technical procedure, with bibliographic support, interviews were performed, questionnaires, field journal and photographic records to collect data, which were analyzed afterwards through content analysis.The locus of the research was the city of Parintins, being 3 Boi-Bumbá top artists the subjects. By conducting this research it was possible to: Comprehend aspects related to giftedness, Criativity e Science; Identify Giftedness Characteristics on the artists who work at Boi-Bumbá in the city of Parintins and reflect on the artist practices and how they knowledge may impact the school. Keywords: High Abilities / Giftedness; Intelligence; Creativity; Science teaching.